Civilizing peace building twenty-first century global politics - Sargent, Wendy M. (Ashgate Pub., 2007)
Sargent highlights the high price paid by the United Nations (UN) and international peace builders that underutilize the reflexive paradigm approach to International Relations (IR). This study develops an overview of IR theory, relied on by governmental and diplomatic communities as a guide to peace building.